Three-dimension kinematics simulation and biomechanics analysis of snatch technique - Bai, X.; Wang, H.; Zhang, X.; Ji, W.; Wang, C. (Proceedings of First Joint International Pre-Olympic Conference of Sports Science and Sports Engineering. Volume I: Computer Science in Sports., 2008)
To analyze various factors restricting weightlifter's squat snatch performance, the squat snatch of a male snatch athlete on active duty was measured and simulated in the computer. Firstly, the anthropometric parameters of a male snatch athlete were measured to be used to parametric transform individualized skeletal system model. Secondly, Optotrak Certus motion capture system (Canada, NDI), 8 Channel EMG System AMT-8 (Canada, bortec) and 3D force measure system (American, bertec) were adopted to synchronically collect the kinematics parameters of squat snatch technique, sEMG signal of 8 representative skeletal muscles and plantar force changes in squat snatch. Thirdly, three dimensional simulation of snatch was realized by tracking markers' coordinates. Finally, the joint angular kinematics, barbell kinematics, external mechanical work and power output in different phases of squat snatch were computed based on kinematics simulation; sEMG signals of 8 representative skeletal muscles and plantar force changes were processed based on the synchronically kinematics simulation. The kinematics and biomechanics characteristics of snatch technique were analyzed and compared through above results to find out the factors restricting weightlifter's performance for providing references to coach and weightlifter athlete.